AN EXAMINATION OF THE OBSTACLES WITH STANDING THE INDIAN STATE OF JAMMU AND KASHMIR’S TOURISM INDUSTRY - Shabir Ahmad Lone; Dr.E.Ravi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
One industry that is thought to be able to spur growth, contribute to foreign exchange, and give low-skilled workers employment is tourism. The exchange of cultures between individuals of different nations and states is one of the key aspects of tourism. As tourism is viewed as both an economic alternative and having a significant social and human impact. The state's unrest, especially in the last 20 years, has hampered tourism's expansion and deterred the majority of tourists from visiting India's most well-known tourist destination. Add to that not only tourism but also the indirect effects of tourism on the economy.